Long-term survival and complications following bladder-preserving brachytherapy in patients with cT1-T2 bladder cancer. (December 2019) - Voskuilen, Charlotte S.; Bosschieter, Judith; van Werkhoven, Erik; Hendricksen, Kees; Vis, André N.; Witteveen, Thelma; Pieters, Bradley R.; Burger, Max; Bex, Axel; van der Poel, Henk G.; Moonen, Luc M.; Horenblas, Simon; et al.
Highlights: Brachytherapy is a bladder-sparing treatment for patients with solitary cT1G3-T2 bladder cancer smaller than 5 cm. Brachytherapy results in a 10-year disease specific survival of 67% in carefully selected patients. The bladder is preserved in the majority of brachytherapy-treated patients. Compared to radical cystectomy, brachytherapy is associated with fewer high grade complications. Abstract: Background and purpose: Radical cystectomy (RC) is considered standard treatment for muscle-invasive bladder cancer (BC) and high-risk non-muscle invasive BC. In selected cases, bladder-sparing treatment using brachytherapy can be offered. We examined the outcome after brachytherapy in comparison to RC in terms of survival, complications and bladder preservation in patients with cT1G3-T2N0M0 BC. Materials and methods: Between 1988 and 2016, 301 patients underwent brachytherapy in two centres. Overall survival (OS) and disease specific survival (DSS) after brachytherapy and RC were assessed using Kaplan-Meier curves. Cox proportional hazards modelling was used to determine variables associated with OS and DSS. Local recurrences, bladder preservation and salvage cystectomy (SC) after brachytherapy were reported. Complications after brachytherapy, RC and SC were compared using CTCAE criteria. Results: Median follow-up was 9.6 years (95% confidence interval (CI): 8.8–10.4) after brachytherapy and 10.6 years (95% CI: 10.0–11.2) after RC. Five/10-year OS was 66%/49% after brachytherapy and 68%/53% after RC ( p = 0.4). Five/10-year DSS was 73%/67% after brachytherapy and 75%/65% after RC ( p = 0.8). Intravesical recurrence occurred in 58/259 brachytherapy patients after which salvage cystectomy was performed in 32 patients. In total, 84% of brachytherapy-treated patients preserved their bladder. The brachytherapy cohort experienced less high grade complications than the RC cohort ( p = 0.02). Conclusion: In selected patients with solitary, ≤5 cm cT1G3-T2N0M0 bladder tumours brachytherapy is a bladder-sparing therapy with good survival outcome and with a favourable complication rate compared to RC.